Efficacy of oblique pulling manipulation combined with adjunct therapies (massage/acupuncture/herbal medicine/injection) for lumbar disc herniation: a systematic review and meta-analysis of pain and functional outcome - Li, Yi; Li, Wenhui; Zhang, Yanting; Zhu, Meiyu; Jiang, Xiaorong; Cai, Xiuqun (Frontiers in Neurology, 2026)
BackgroundThis study aimed to systematically evaluate the clinical efficacy of oblique pulling manipulation and its combination with massage, acupuncture, Chinese herbal medicine, and injection therapy in lumbar disc herniation (LDH).MethodsThe meta-analysis followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and was registered with PROSPERO (CRD420251107984). A comprehensive search was conducted in databases including China National Knowledge Infrastructure (CNKI), Wanfang Database, Chinese Scientific Journals Database (VIP), Chinese Biomedical Literature Database (CBM), PubMed, EMBASE, Web of Science, and the Cochrane Library until June 2025. All statistical analyses were conducted using Review Manager 5.4.1. Dichotomous outcomes were summarized as odds ratios (ORs) with 95% confidence intervals (CIs), and continuous outcomes were summarized as standardized mean differences (SMDs) with 95% CIs.ResultsA total of 26 studies comprising 2,766 patients with lumbar disc herniation were included. The results of the meta-analysis revealed that oblique pulling manipulation and its combination with massage, acupuncture, Chinese herbal medicine, and injection therapy in LDH significantly improved the effective rate and cure rate in patients with LDH. In addition, oblique pulling manipulation significantly improved the Japanese Orthopedic Association (JOA) score, and oblique pulling manipulation combined with massage or acupuncture decreased the Oswestry Disability Index (ODI).DiscussionOblique pulling manipulation and its combination with massage, acupuncture, Chinese herbal medicine, and injection therapy improved efficacy and cure rates in patients with lumbar disc herniation. Future research should focus on standardizing treatment protocols and extending follow-up periods to confirm long-term safety and effectiveness, thereby ensuring broader applicability and better patient outcomes.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/CRD420251107984, identifier: CRD420251107984.